IMPLEMENTASI PEMENUHAN DAN PERLINDUNGAN HAK ASASI MANUSIA DALAM SISTEM PERADILAN PIDANA INDONESIA (Institut Pemerintahan Dalam Negeri, 2020)
The making of this journal aims to ϔind out about (1) How to regulate human rights in Indonesian laws and regulations (2) What is the form of the protection and application of human rights in the criminal justice system according to Law No. 8 of 1981 (KUHAP). To answer this problem, the writer uses normative research methods; comprehensive analytical study of primary and secondary legal materials. The results of the study show that the basis for regulating human rights has been formulated in the Criminal Procedure Code and has brought renewal in regulating human rights as stipulated in articles on the rights of suspects / defendants and also regulates the principles that support human rights Humans such as the Pre-Guilty Principle Principle, and also presuppose a very fundamental legal principle, the principle of Equality in Law is known as Equality Before The Law. Theoretically, from the stage of investigation, prosecution and examination before a court hearing. But in reality there are still violations committed by individual law enforcement officers. Keywords: Regulations on the Application of Human Rights, Regulations and Regulations, the Criminal Justice System